Perlindungan Hukum Terhadap Nasabah Atas Kejahatan Phising pada Mobile Banking Perspektif Maqashid Syariah: Studi Kasus di BSI KCP Gatot Subroto - Siti Rahayu; Fatimah Zahara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of mobile banking services offers convenience to customers but also increases the risk of cybercrimes, such as phishing, which can lead to financial losses. This study aims to analyze the legal protections and bank liability regarding losses suffered by customers who fell victim to phishing while using the BSI KCP Gatot Subroto mobile banking service, as well as to examine the issue from the perspective of maqashid sharia (the objectives of Sharia). The research employs an empirical-juridical method utilizing qualitative, conceptual, and statutory approaches. Data were gathered through literature reviews and interviews with BSI KCP Gatot Subroto customer service staff and customers who had been victims of phishing. The findings indicate that protection is provided through preventive measures—such as education and system security enhancements—and repressive measures, including complaint handling, investigations, and the blocking of account access. However, the recurrence of phishing incidents in 2023, 2024, and 2025 suggests that these protective measures have not been fully effective. In the cases studied, the bank attributed the losses to customer negligence without conducting a transparent assessment of the bank's own security system effectiveness. From the perspective of maqashid sharia, such protection relates to the principle of hifz al-mal (preservation of wealth), although its implementation has not yet been fully optimal.